Sanitation practices targeting overwintering inoculum improve management of strawberry powdery mildew in high-tunnel production - Aldrighetti, Anna; Zott, Davide; Pertot, Ilaria (Frontiers in Agronomy, 2026)
Strawberry powdery mildew, caused by Podosphaera aphanis, is a major disease of strawberry, capable of leading to yield losses of up to 70%. Its management typically relies on frequent chemical fungicide applications due to the extended infection window of the pathogen. Podosphaera aphanis overwinters as mycelium and chasmothecia on infected plant material, which may act as primary inoculum in spring. This two-year study investigated the effectiveness of post-winter removal of infected leaf and plant debris in disease control and quantified the role of chasmothecia in early season infection under high-tunnel conditions. Complete removal of infected tissues delayed disease onset and reduced severity by up to 88%. In the two years, chasmothecium formation increased in late summer following 8 and 16 cumulative hours below 13 °C, respectively. In spring, ascosporic infection events occurred after the accumulation of 21 and 18 cumulative hours with temperatures above 10 °C combined with at least two consecutive hours of leaf wetness, consistently with previous findings. The efficacy of the sanitation practice was further supported by excluding the possibility that chasmothecia and/or chasmothecia on debris fragments potentially fallen into the substrate could trigger infection. In addition, we investigated the timing of ascospore-derived infections by monitoring disease progression on individual leaves. Infection rate was quantified across different leaf ages to assess their role in epidemic development and their potential contribution to secondary inoculum. The highest infection rate was observed on 15-day-old class age, with a crucial role in supporting early pathogen development. These results indicate the importance of sanitation practices, such as overwintering infected leaf removal in reducing early-season infections and informing more targeted control strategies.